Kehidupan di Tepi Sungai Batang Arau dalam Karya Seni Grafis - Rezki Pratama; Yofita Sandra (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
The purpose of the creation of this work is as social criticism and conveying messages about river pollution behavior that occurs in the Batang Arau river in Padang city by visualizing the impact of river pollution on humans. which is poured into graphic artworks. The creation of the work uses the art consortium method with five stages, namely, the preparation stage (observation and exploration), the elaboration stage (searching and collecting references), the synthesis stage (application of main ideas), the realization of concepts (making works), and the completion stage (artist report and final work exhibition).So that the realization of ten works that the author made with the theme of the impact of river pollution, the resulting works are 10 works with a size of 55 x 40 cm with titles including: Hal Baik yang Terganggu, Blind, Seiring Sejalan, Tanpa Sadar, Ingin Tapi Tak Bisa, Malam yang Sulit, Dimatanya, Meniru, Luapan, Dari dan untuk diri sendiri.